Lay-Spirituality Among the Modernists: Friedrich von Hügel - Neuner, Peter (Philosophy & theology, 1989)
The riddle of Baron von Hugel has always been how to reconcile his deep piety and attractiveness as a spiritual writer with his austere use of historical criticism on biblical texts. By interpreting Roman Catholic Modernism as basically a development in the history of piety, validating the turn to the subject of modern philosophy and science, one sees that von Hugel’s life is all of a piece, with his criticism and theology rooted in what he called “the mystical element.” Thus investigation of von Hugel’s spiritual theology leads to a new interpretation of the Modernist movement as a whole.